Exploring the Necessity of Psychological Rounds and Psychological Interventions in General Hospitals in the Post-COVID-19 Period - Tang, PeiXi; Lee, MaoSheng (Frontiers in Psychology, 2022)
Objective: To explore the necessity of psychological rounds and psychological intervention in post-COVID-19 period in general hospital. Methods: Based on the current pandemic influence on Chinese people's psychology, the medical experience and environment were analyzed, and the feasibility of psychological evaluation and intervention were appraised with the psychological changes that might be brought by the medical behavious, especially for surgical operations. Results: Nowadays, the pandemic is under-full-control in China although the pandemic is rampant abroad. In China, the "Normalized pandemic prevention" phase has begun. In the post-COVID-19 period, the prolonged pandemic has made numerous people pessimistic, angry and other negative emotions. Number of general hospitals are facing a huge influences: Under the influence of anxiety such as "higher hospital acquired infection rate", the patient attendance rate is reduced, and the hospital income is sharply reducing; Doctor-patient conflicts are more likely to occur in the medical procedures, affecting the medical experience, and reducing the rate of re-visit and referral. Conclusion: After analyzing a series of "endogenous" and "exogenous" factors of medical procedures in general hospital in post-pandemic period, it suggests that anxiety and depression caused by uncertainties in the medical procedures maybe more obvious. And it is necessary to pay attention to the psychological status of patients, carry out psychological rounds and psychological intervention in general hospital. The service quality can be improved and the medical experience can be ameliorated, and It can help general hospital turn "crisis" into "opportunity", which also bring to better development.